Cross-cultural adaptation of the Leg Ulcer Measurement Tool for Brazil: nursing methodology research - Silveira,Isabelle Andrade (2020)
ABSTRACT Objectives: to translate and cross-culturally adapt the Leg Ulcer Measurement Tool to Brazilian Portuguese. Methods: methodological study involving the steps of initial translation, synthesis of translations, back-translation, expert panel and pretest. For analysis by the expert committee, the content validity index was calculated and in the pretest for practicality, the agreement rate was calculated. Satisfactory agreement was considered when > 0.8 and 80%, respectively. Results: the initial steps of translation were satisfactorily developed and there was little disagreement between the translators. In the expert panel, was obtained significant concordance of 0.97. The pretest was performed with ten nurses and 30 patients. The feasibility of the translated version was evaluated with 100% agreement. Final Considerations: the instrument presented a high level of concordance among the experts during all steps and showed content validity thereby making the adaptation appropriate for the Brazilian context.